HDAC6 differentially regulates autophagy in stem-like versus differentiated cancer cells. Issue 4 (3rd April 2019) - Sharif, Tanveer; Martell, Emma; Dai, Cathleen; Ghassemi-Rad, Mohammad Saleh; Hanes, Mark Robert; Murphy, Patrick J.; Margam, Nandini N.; Parmar, Hirendrasinh B.; Giacomantonio, Carman A.; Duncan, Roy; Lee, Patrick W.K.; Gujar, Shashi
ABSTRACT: Cancer stem-like cells (CSCs), a small population of pluripotent cells residing within heterogeneous tumor mass, remain highly resistant to various chemotherapies as compared to the differentiated cancer cells. It is being postulated that CSCs possess unique molecular mechanisms, such as autophagic homeostasis, that allow CSCs to withstand the therapeutic assaults. Here we demonstrate that HDAC6 inhibition differentially modulates macroautophagy/autophagy in CSCs as compared to that of differentiated cancer cells. Using human and murine CSC models and differentiated cells, we show that the inhibition or knockdown (KD) of HDAC6 decreases CSC pluripotency by downregulating major pluripotency factors POU5F1, NANOG and SOX2. This decreased HDAC6 expression increases ACTB, TUBB3 and CSN2 expression and promotes differentiation in CSCs in an apoptosis-independent manner. Mechanistically, HDAC6 KD in CSCs decreases pluripotency by promoting autophagy, whereas the inhibition of pluripotency via retinoic acid treatment, POU5F1 or autophagy-related gene ( ATG7 and ATG12 ) KD in CSCs decreases HDAC6 expression and promotes differentiation. Interestingly, HDAC6 KD-mediated CSC growth inhibition is further enhanced in the presence of autophagy inducers Tat-Beclin 1 peptide and rapamycin. In contrast to the results observed in CSCs, HDAC6 KD in differentiated breast cancer cells downregulates autophagy and increases apoptosis. Furthermore, the autophagy regulator p-MTOR, upstream negative regulators of p-MTOR (TSC1 and TSC2) and downstream effectors of p-MTOR (p-RPS6KB and p-EIF4EBP1) are differentially regulated in CSCs versus differentiated cancer cells following HDAC6 KD. Overall these data identify the differential regulation of autophagy as a molecular link behind the differing chemo-susceptibility of CSCs and differentiated cancer cells.